(untitled) (Academia Journal of Medicine, 2022)
This paper explores the remarkable advancements that have reshaped the field of orthodontics, ushering in an era of precision, efficiency, and patient-centered care. From digital technology and invisible orthodontic solutions to 3D printing and AI-driven treatment planning, the evolution of orthodontics has redefined treatment strategies and enhanced clinical outcomes. This comprehensive review highlights the transformative technologies that have revolutionized orthodontic practice, ultimately improving patient experiences and treatment effectiveness.